Hijaiyyah Learning Transformation: Effectiveness of the Digital Iqra Application at Bungong Seulanga Kindergarten Pidie Jaya - Hasballah, Jamaliah; Rahmah, siti Rahmah (Kiddie: Early Childhood Education and Care Journal, 2024)
As science and technology develop, there is an urge to utilize technology in the learning process. TeachersÂ Â  are required to use existing tools in accordance with current developments. One of them is the Iqra Digital application such as Marbel Mengaji to introduce hijaiyyah letters to children. Based on initial observations at the Bungong Seulanga Pidie Jaya State Kindergarten, some children cannot read the hijaiyyah letters properly and correctly, and their understanding is still weak. This research uses quantitative methods with a one group pretest-posttest design. The research sample was total sampling, involving all children in class A (16 children). Data collection was carried out through observation sheets and documentation. The research results show a significant increase in the recognition of hijaiyyah letters through the application of the Iqra Digital (Marbel Mengaji) application. The t-test results show tcount of 14,679 and ttable of 2,131 with degrees of freedom (df) 15 at the significance level Î± = 0.05. These results indicate that Ha was accepted and Ho was rejected, which means that the application of the Iqra Digital application is effective in improving children's ability to recognize hijaiyyah letters. Seiring berkembangnya ilmu pengetahuan dan teknologi, maka muncul dorongan untuk memanfaatkan teknologi dalam proses pembelajaran. Guru dituntut untuk menggunakan alat-alat yang ada sesuai dengan perkembangan zaman. Salah satunya adalah aplikasi Iqra Digital seperti Marbel Mengaji untuk mengenalkan huruf hijaiyyah kepada anak. Berdasarkan observasi awal di TK Negeri Bungong Seulanga Pidie Jaya, sebagian anak belum bisa membaca huruf hijaiyyah dengan baik dan benar, serta pemahaman mereka masih lemah. Penelitian ini menggunakan metode kuantitatif dengan desain one group pretest-posttest. Sampel penelitian adalah total sampling, melibatkan seluruh anak di kelas A (16 anak). Pengumpulan data dilakukan melalui lembar observasi dan dokumentasi. Hasil penelitian menunjukkan peningkatan secara signifikan dalam pengenalan huruf hijaiyyah melalui penerapan aplikasi Iqra Digital (Marbel Mengaji). Hasil uji-t menunjukkan thitung sebesar 14.679 dan ttabel sebesar 2.131 dengan derajat kebebasan (df) 15 pada taraf signifikan Î± = 0,05. Hasil ini menunjukkan bahwa Ha diterima Ho ditolak, yang berarti bahwa penerapan aplikasi Iqra Digital efektif dalam meningkatkan kemampuan anak mengenal huruf hijaiyyah.